PROFESSIONAL TRAINING OF PSYCHOLOGISTS: THE NEED FOR STRUCTURAL TRANSFORMATIONS - Irina V. Tkachenko (Высшее образование в России)
The article examines the quality of training in educational institutions and also identifies the areas requiring new approaches, which affect the human involvement in the professional activity, the accumulation of personal positive experiences of its implementation, the successful acquisition of professional competences and sense attitude to the profession.